Moenkhausia venerei (Characiformes: Characidae), a new species from the rio Araguaia, Central Brazil - Petrolli, Marina G.; Azevedo-Santos, Valter M.; Benine, Ricardo C. (Zootaxa, 2016)
Moenkhausia venerei is described from the rio Araguaia, Mato Grosso, Central Brazil. The new species differs from its congeners, except M. collettii and M. copei, by the combination of the following characters: a longitudinal dark band extending from the tip of the snout to the base of caudal fin; a dark line along the base of the anal fin; and a conspicuous humeral spot. Moenkhausia venerei is distinguished from M. collettii by having a wider and more conspicuous longitudinal dark band and from M. copei by the higher number of anal-fin rays. A discussion about the overall similarity and putative relationship with M. collettii, M. copei, Hemigrammus ulreyi, H. ataktos, and H. barrigonae is provided.